Earthquake Archaeology: A Future in Ruins? - Jusseret, Simon (Journal of Contemporary Archaeology, 2015)
Earthquake archaeology, also known as archaeoseismology, is traditionally defined as the discipline investigating the effects of earthquakes on ancient archaeological remains. As a research field geared towards the definition of seismic parameters for past earthquakes, earthquake archaeology’s social role is often overlooked. However, earthquake archaeology can foster earthquake preparedness by communicating to present-day communities how past populations occupying similarly threatened areas coped with seismic events. In this paper, I argue that the discipline might also fulfil this social responsibility by emphasizing the applicability of earthquake archaeological methodologies, particularly those borrowed from archaeology, to contexts struck by recent (i.e. twentieth and twenty-first century) earthquakes. By doing so, earthquake archaeology could play a crucial part in prevention and mitigation efforts. Four possible mechanisms underpinning such a socially-engaged earthquake archaeological discipline are discussed: manifestation, restoration, acting with and on behalf of affected communities and mediation between past and present.